VARIABEL PENENTU DAN EKSKALASI JUMLAH TABUNGAN MUDHARABAH DI BRI SYARIAH CABANG JEMBER - Ahmad Roziq; Ika Ratna Qorikaten Rohmah (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2016)
The aim of this study was to to examine and analize the confidence level, return of profit sharing, the suitability of sharia law, the reputation of the bank and the acquisition of information influence significantly affect the amount of Mudharabah savings in branch of BRI Syariah Jember. This research is a quantitative research with using type of explanatory research. The results showed that the level of trust significantly influence the amount of Mudharabah savings. Suitability sharia law significantly influence the amount of Mudharabah savings. The bank’s reputation significantly influences the amount of Mudharabah savings. Information obtained customers significantly influence on the amount of savings at BRI Syariah Jember with a positive direction.